Soil CO2 efflux of oil palm and rubber plantation in 6-year-old and 22-year-old chronosequence - Sigau, Cindy Usun; Abdul Hamid, Hazandy (Universiti Putra Malaysia Press, 2018)
Soil CO2 efflux, in relation with chronosequence at oil palm and rubber plantations, was measured monthly, each with both 6- and 22-year-old stands. Other environmental factors such as soil temperature and relative humidity (RH), as well as soil properties, were also measured at 0–30 cm depth. Soil CO2 efflux was found to be highly affected by forest types and chronosequence factor. The 22-year-old age stand (M = 0.91; SD = 0.17 g CO2 m−2 h−1) had significantly higher soil CO2 efflux than the 6-year-old stand (M = 0.54; SD = 0.18 g CO2 m−2 h−1). Soil RH plays a significant role controlling soil CO2 efflux compared with soil temperature, especially at younger stands of tropical oil palm and rubber plantations spatially. Lower Q10 values were found to be caused by higher temperature that had reduced enzymatic and substrates activities for soil respiration. Non-discernible trends of temporal soil CO2 efflux, soil temperature, and RH indicated that other significant factors could be the catalyst, and thus further research is required to explain the relations between soil CO2 efflux and environmental factors. Research findings indicated that older stand age of oil palm and rubber plantations in Malaysia released higher soil CO2 efflux, but with no degrading effects towards the environment.